Astrology a beginner's guide - Boston, Graham (Headway, 1998)
A guide to drawing up your own birth chart and interpreting the position of the sun, moon and planets for character reading. Information is also given about relationship compatibilities and predicting future life events. Examples are given of internationally-known figures and world events.